(untitled) (The International Journal for Scientific Research, 2025)
The current study aimed to reveal the level of religious commitment and psychological resilience, and to understand the relationship between religious commitment and psychological resilience among a sample of people with visual and motor disabilities in Idlib Governorate. The study sample consisted of (92) people with disabilities in northwestern Syria, distributed among two centers for people with disabilities in Idlib city. The study was based on two scales: religious commitment prepared by the researchers, and psychological resilience by Connor and Davidson 2003, translated and standardized by Abdul Aziz Musa Muhammad Thabet. The results of the study indicated that the level of both religious commitment and psychological resilience was high, that there was a positive correlation between religious commitment and psychological resilience, and that there were differences in the level of religious commitment and psychological resilience according to the variable of type of disability (visual, motor) in favor of visual.